2017
DOI: 10.1136/bmjopen-2016-014314
|View full text |Cite
|
Sign up to set email alerts
|

Increasing general practitioners' confidence and self-efficacy in managing obesity: a mixed methods study

Abstract: ObjectivesInternationally, general practitioners (GPs) are being encouraged to take an active role in the care of their patients with obesity, but as yet there are few tools for them to implement within their clinics. This study assessed the self-efficacy and confidence of GPs before and after implementing a weight management programme in their practice.DesignNested mixed methods study within a 6-month feasibility trial.Setting4 urban general practices and 1 rural general practice in Australia.ParticipantsAll … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 24 publications
0
51
0
Order By: Relevance
“…As shown in Table S3, seven studies did not report any patient characteristics . Four studies reported on age and gender but did not provide any information on socio‐economic status (SES) or ethnicity .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown in Table S3, seven studies did not report any patient characteristics . Four studies reported on age and gender but did not provide any information on socio‐economic status (SES) or ethnicity .…”
Section: Resultsmentioning
confidence: 99%
“…There were a range of outcomes measured in the 30 studies, although most included at least one of the key outcomes of interest to this review, namely: Discussion of weight (including lifestyle advice); Measuring and recording of weight and/or BMI; and Referral to WMS …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations